2021
DOI: 10.1111/ffe.13480
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Failure Assessment Diagram approach for contact fatigue damage evaluation in railway wheel steels

Abstract: A Failure Assessment Diagram (FAD), developed for rolling contact, was specifically formulated for railway wheel steels. The FAD allows combining a multiaxial fatigue criterion with the linear elastic fracture mechanics concept; in particular, it was used to assess the fatigue failure in wet contact, related to the pressurization of the fluid entrapped in surface cracks. The approach was applied to the results of previous bi‐disc tests carried out on three railway wheel steels, subjected first to a dry rolling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…1,2 With the increasing running speeds and axle loads in modern railways, a new challenge of shattered rims is posed to the wheel/rail pair. 3,4 Shattered rim is a form of rolling contact fatigue caused by subsurface and interior crack initiation. [5][6][7][8] In general, fatigue life of shattered rim was usually more than 10 7 cycles, indicating a typical VHCF under rolling contact loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 With the increasing running speeds and axle loads in modern railways, a new challenge of shattered rims is posed to the wheel/rail pair. 3,4 Shattered rim is a form of rolling contact fatigue caused by subsurface and interior crack initiation. [5][6][7][8] In general, fatigue life of shattered rim was usually more than 10 7 cycles, indicating a typical VHCF under rolling contact loading.…”
Section: Introductionmentioning
confidence: 99%
“…The new research topic of very‐high‐cycle fatigue (VHCF) is drawing increased attention because many engineering components, such as high‐speed railway wheels, turbine blades, and automobile cylinders, require 10 8 or even more loading cycles for safe performance 1,2 . With the increasing running speeds and axle loads in modern railways, a new challenge of shattered rims is posed to the wheel/rail pair 3,4 . Shattered rim is a form of rolling contact fatigue caused by subsurface and interior crack initiation 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that these cracks can be approximated as an ellipse with a diameter ratio of 2.5 to 7. Donzella et al 13 used a specified failure assessment diagram approach for the railway wheel steel to assess fatigue life prediction in wet contact conditions. Their numerical results were in agreement with the observed damages in cross‐sections of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on crack propagation and fatigue analysis have been conducted. [9][10][11][12][13][14][15][16][17] Sajjadi et al 18 put forward a new brittle fracture criterion to predict the fracture in sharp V-shaped notches considering the influence of tangential stress and shear stress, which can effectively describe the situation where mode II load is dominant. Peixoto and de Castro 9 established a two-dimensional, wheel-rail contact, finite element model and discovered that the crack growth mode of the wheel rim is II or I-II mixed crack propagation mode dominated by shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…Nejad et al 13 analyzed the influence of mechanical loads and stress fields during heat treatments on rim crack growth by establishing a three-dimensional, wheel-rail contact, finite element model to be combined with stress history to calculate mode I, II, and III stress intensity factors at the crack tip, as well as the wheel fatigue life. Donzella et al 14 proposed a calculation procedure for assessing mixed mode crack propagation and applied the procedure to railway wheels.…”
Section: Introductionmentioning
confidence: 99%